'Alien Hieroglyphs of Eternity' and 'Cold Pastorals': Allen Ginsberg's 'Siesta in Xbalba' and John Keats's Great Odes. (1st September 2013) - Bellarsi, Franca
Abstract : Examining the poetry of Allen Ginsberg in the light of that of John Keats, the possible connections between 'Siesta in Xbalba' — a long poem by Ginsberg that received much more critical attention in the eighties than today — and Keats's so-called Great Odes are investigated. 'Siesta' is here read as a composite mainly recycling 'Ode on a Grecian Urn' and 'Ode to a Nightingale', whose themes and motifs Ginsberg both preserves and subverts. This is the first attempt to conflate 'Siesta' with Keats's Great Odes.